Selective inhibition of Rab prenylation by a phosphonocarboxylate analogue of risedronate induces apoptosis, but not S-phase arrest, in human myeloma cells. - Roelofs, A; Hulley, P; Meijer, A; Ebetino, F; Russell, R; Shipman, C (2006)
Bisphosphonates (BPs) are widely used in the treatment of osteolytic bone disease associated with multiple myeloma, and have been demonstrated to exert antitumor effects both in vitro and in vivo. However, the precise molecular mechanisms involved in the direct antitumor effects of BPs in vitro are not known. Nitrogen-containing BPs, such as risedronate (RIS), act by inhibiting protein prenylation. A phosphonocarboxylate analogue of RIS, 3-PEHPC, has previously been shown in osteoclasts and macrophages to specifically inhibit prenylation of Rab GTPases. The aim of this study was to identify the molecular targets of RIS and 3-PEHPC in human myeloma cells and to determine the cellular effects of selective inhibition of Rab prenylation by 3-PEHPC as compared to nonspecific inhibition of protein prenylation by RIS in human myeloma cells. RIS dose-dependently inhibited prenylation of both Rap1A and Rab6, whereas 3-PEHPC only inhibited Rab6 prenylation. Both RIS and 3-PEHPC dose-dependently increased apoptosis in human myeloma cells. RIS induced an accumulation of cells in the S-phase of the cell cycle, associated with inhibition of DNA replication. In contrast, 3-PEHPC did not cause cell-cycle arrest. Furthermore, geranylgeraniol could prevent inhibition of prenylation, induction of apoptosis, and cell-cycle arrest in response to RIS, but not inhibition of Rab prenylation and apoptosis induced by 3-PEHPC, consistent with specific inhibition of Rab geranylgeranyl transferase by 3-PEHPC. In conclusion, our studies demonstrate that selective inhibition of Rab prenylation induces apoptosis, but not S-phase arrest, thus identifying distinct molecular pathways that mediate the antimyeloma effect of nitrogen-containing BPs.